The prevalence of community programmes and policies to prevent childhood obesity in a diverse sample of US communities: the Healthy Communities Study. (1st October 2018) - Collie‐Akers, V. L.; Schultz, J. A.; Fawcett, S. B.; Obermeier, S. M.; Pate, R. R.; John, L. V.; Weber, S. A.; Logan, A.; Arteaga, S. S.; Loria, C. M.; Webb, K.; ,
Summary: Introduction: This manuscript describes the prevalence and attributes of community programmes and policies (CPPs) to address childhood obesity documented as occurring in 130 diverse US communities. Methods: Key informant interviews ( N = 1420) and document abstraction were used to identify and characterize CPPs to promote physical activity and healthy nutrition occurring during a 10‐year retrospective study period. Data were collected in 2013–2015 and analysed in 2016. Results: Across all 130 communities, 9681 distinct CPPs were reported as occurring by key informants. Of these, 5574 (58%) focused on increasing physical activity, 2596 (27%) on improving nutrition and 1511 (16%) on both behaviours. The mean number of CPPs per community was 74.0, with a range of 25 to 295 across all communities. Most CPPs occurred more than once (63%) and on average lasted 6.1 years. The greatest number of reported CPPs occurred in school settings (44%). Conclusions: Communities showed a wide range of investment in the amount of CPPs occurring in settings that affect opportunities for children to engage in physical activity and healthy nutrition. The pattern of implementation of CPPs showed variation over time, with an increase in more recent years. This observational study provides new and valuable information about what US communities are doing to prevent childhood obesity. Abstract : What is already known about this subject? With increases in childhood obesity, agenda‐setting organizations and federal initiatives have called for comprehensive approaches involving multiple community programs and policies. Community efforts to address childhood obesity have included programs, policies, and environmental changes to promote physical activity and healthy nutrition. Little is known about the amount and kind of community programs and policies actually being implemented in communities throughout the U.S. What this study adds? This study provides data on the observed prevalence of community programs and policies addressing childhood obesity in a diverse sample of 130 U.S./ communities. It shows that the observed number of community programs and policies increased in more recent years, with more marked increases seen after 2009. It shows that the observed length of community programs/ policies and types of behavioral objectives targeted varied substantively across communities; while other variables, such as reach or target, were more similar across programs and policies. This article is part of the supplement: The Healthy Communities Study: Examining Community Programs, Policies and Other Characteristics in Relation to Child Weight, Diet, and Physical Activity